Epidemiology of genital infections caused by Mycoplasma hominis, M. genitalium and Ureaplasma urealyticum in Iran; a systematic review and meta-analysis study (2000-2019) - Khadijeh Moridi; Mohammad Hemmaty; Amir Azimian; Mohammad Hosein Fallah; Hamid Khaneghahi Abyaneh; Kiarash Ghazvini (BMC, 2020)
Abstract Background Although many species of mycoplasmas regard as normal flora, but some species causes serious genital disease. In Iran several epidemiological studies have documented the prevalence of Mycoplasma hominis, M. genitalium and Ureaplasma urealyticum in genital disorders. This meta-analysis is going to represent the prevalence of M. hominis, M. genitalium and U. urealyticum among Iranian couples and the correlation between mycoplasmas infection and infertility. Methods We search online databases from January 2000 to June 2019. We used following MeSH keywords (Prevalence, M. hominis, M. genitalium, U. urealyticum, male, female, fertility, Infertility, genitourinary tract infection and Iran) with all possible combinations with "OR" and "AND". Finally, forty-four articles from 2670 were chosen for data extraction and analysis by software using STATA version 14.0. Results This meta-analysis revealed that the prevalence of U. urealyticum was 17.53% in Iran and the prevalence of M. genitalium and M. hominis were 11.33 and 9.68% respectively. The rate of M. genitalium, M. hominis and U. urealyticum infection in women with symptoms of genitourinary tract infection was higher than men with genitourinary tract infection (6.46% vs 5.4, 7.67% vs 5.88 and 21.04% vs 12.13%, respectively). As expected, the prevalence of M. genitalium, U. urealyticum and M. hominis among infertile women (12.73, 19.58 and 10.81%) were higher than fertile women (3%, 10. 85% and 4. 35%). Similarly, the prevalence of M. hominis and U. urealyticum among infertile men (14 and 21.18%) were higher than fertile men (4 and 3%). Based on this analysis, the rate of U. urealyticum was higher than M. genitalium and M. hominis among infertile men and women compared to the fertile group. The prevalence rate of M. genitalium, M. hominis and U. urealyticum in central provinces is higher than other parts of Iran. Conclusions This meta-analysis reemphasizes a significant relationship between the infertility rate and U. urealyticum, M. genitalium and M. hominis infections. Our finding help to plan the prevalence map of M. hominis, M. genitalium and U. urealyticum in Iran but further studies are needed to suggest routine screening of the pathogens.